(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was conducted to isolate and identify the organisms in butter and cheese manufactured by different plants namely Milk Vita and Quality sold in retail stores at Dinajpur, Bangladesh were collected and transported aseptically to the laboratory for bacteriological analyses. The samples were analyzed to determine the hygienic status of butter and cheeses and also for the total viable count (TVC), presence of gram-positive and gram-negative bacteria. TVC was performed according to the American Public Health Association, using plate count agar medium for TVC and Eosine methylene blue (EMB) agar for total E. coli count and Staphylococcus agar no. 110 for total Staphylococcus count. The average TVC for Milk Vita butter 3.28 x 105 CFU/gm (log 5.5) was lower than local butter 5.45 x 106 CFU/gm (log 6.7) and average TVC for Quality cheese 4.5 x 105 CFU/gm (log 5.7) was lower than local cheese 5.14 x 106CFU/gm (log 6.7). The bacterial loads of butter and cheese samples were within the acceptable limit of public health safety, since the count was well below the acceptable limit. The highest extent of bacterial contamination and proliferation of viable bacteria occurred in local butter and local cheese. The numbers of E. coli in local butter and cheese were little bit higher indicating poor hygienic practices during manufacture, post process contamination and unsatisfactory transportation. Statistically the E. coli were more closely related to TVC than the staphylococcal counts in the samples of Milk Vita butter 2.68 x 103 CFU/gm (log 3.4), Local butter 3.15x 104 CFU/gm (log 4.5), Quality cheese 4.46 x 103 CFU/gm (log 3.6) and Local cheese 1.19 x 104 CFU/gm (log 4.0) respectively. The results demonstrated that Milk Vita butter and Quality cheese are of superior quality product in respect of sanitary condition. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 504-513